2020
DOI: 10.3390/nano10020201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Structure, Composition, and Electrocatalytic Performance of Hydrogen Evolution in MoSx~2+δ/Mo and MoSx~3+δ Films Obtained by Pulsed Laser Deposition

Abstract: Systematic and in-depth studies of the structure, composition, and efficiency of hydrogen evolution reactions (HERs) in MoSx films, obtained by means of on- and off-axis pulsed laser deposition (PLD) from a MoS2 target, have been performed. The use of on-axis PLD (a standard configuration of PLD) in a buffer of Ar gas, with an optimal pressure, has allowed for the formation of porous hybrid films that consist of Mo particles which support a thin MoSx~2+δ (δ of ~0.7) film. The HER performance of MoSx~2+δ/Mo fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…This circumstance may explain the formation of a rather dense structure in the deposited MoS x coatings. If the ion bombardment of MoS x coatings (which are formed through the deposition of Mo and S atoms) is absent or ineffective, there is a tendency toward a porous column structure with a cauliflower morphology [37]. Figure 2 shows the results of the XRD studies of MoS x coatings.…”
Section: The Structure and Composition Of Mos X Filmsmentioning
confidence: 99%
“…This circumstance may explain the formation of a rather dense structure in the deposited MoS x coatings. If the ion bombardment of MoS x coatings (which are formed through the deposition of Mo and S atoms) is absent or ineffective, there is a tendency toward a porous column structure with a cauliflower morphology [37]. Figure 2 shows the results of the XRD studies of MoS x coatings.…”
Section: The Structure and Composition Of Mos X Filmsmentioning
confidence: 99%
“…With such complex distributions seen for all investigated plasmas with multiple maxima and possible NP-induced structures, the control of plasma energy during the deposition becomes essential. Several routes for controlling the plasma kinetics are proposed in the literature including but not limited to fluence reduction [ 2 , 36 ], background gas addition [ 22 , 37 , 38 ], off-axis deposition [ 39 ], etc. The control from laser fluence can be challenging as changes in the transferred energy towards the target strongly affects the fundamental ablation mechanisms and often leads to the formation of clusters and droplets on the deposited film [ 40 , 41 ], which is undesirable.…”
Section: Resultsmentioning
confidence: 99%
“…Experiential studies of amorphous molybdenum sulfide (a-MoS x ) catalytic film creation have shown that, during off-axis PLD, the buffer gas has the conditions necessary for the effective saturation of films with chalcogen atoms [28]. These conditions are a result of the difference between the S and Mo atomic masses.…”
Section: Introductionmentioning
confidence: 99%
“…The most common technique to obtain such films is a chemical synthesis or chemical deposition in the solutions of special precursors. The applicability of a laser-based technique to create amorphous a-MoS x films with good electrocatalytic properties has been described in the literature [28,[32][33][34][35]. Fominski et al demonstrate that the PLD technique is associated with the highest catalytic activity in MoS x~4 films because they contain Mo 3 S 12 /Mo 3 S13 clusters [35].…”
Section: Introductionmentioning
confidence: 99%